Etika Siaran Iklan: Analisis Pelanggaran Jam Tayang di Media Televisi - Azriel Raisian; Muhammad Arif Aprihatno; Irfandi Ardiansyah Handoko; Daniel Handoko (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This research analyzes the ethics of broadcasting advertisements on television media, especially related to broadcasting time regulations. The significant role of television in shaping people's thoughts and behaviors, coupled with the proliferation of potentially unethical and inappropriate broadcasts, highlights the urgency of this issue. Such violations, especially those concerning children and adolescents, pose significant risks due to exposure to inappropriate content and the normalization of unethical behavior. This study emphasizes the importance of media commitment to the Broadcasting Behavior Guidelines and Broadcast Program Standards (P3SPS) and Law No. 32 of 2002, which aims to protect viewers from harmful information. This study uses a library observation method with a qualitative approach, analyzing existing reports, research, and written sources. Data analysis uses Miles and Huberman's qualitative decomposition technique, which includes data reduction, data presentation, and drawing conclusions. The findings of the study are in line with previous studies, indicating that violations of broadcasting ethics and broadcasting hours are systemic problems that have not been resolved. This underlines the need for stricter supervision, sanctions, re-evaluation of broadcasting time classifications, and media literacy education for the community.